Factors Causing Stock-Outs and Drug Stagnation at Pharmacy Installation of Puri Bunda Mother and Child Hospital Malang - Tri Utami, Ni Nyoman Ayu; Ratri, Devita Rahmani; Nuthea, Merry (Jurnal Kedokteran Brawijaya, 2021)
Hospital pharmacy service is a supporting service as well as a revenue center in a hospital. More than 90% of hospital services utilize pharmaceutical supplies, and 50% of hospital revenues originate from pharmaceutical supply management. In the Covid-19 pandemic situation, the pharmacy installation must calculate the logistics management of the medicine correctly. However, based on stocktaking in May-July at Puri Bunda Mother and Child Hospital, there were stock-outs (4.06%) and drug stagnation (2.44%) due to poor drug procurement, causing declining drug sales. This study analyzed the factors causing stock-outs and drug stagnation in the Pharmacy Installation of Puri Bunda Mother and Child Hospital. This study uses a descriptive approach with data collection methods using observations, Focus Group Discussion (FGD), and Likert-scale questionnaires to find the roots of the problems. The data were analyzed using the Fishbone Diagram and Pareto Diagram. The research subjects based on total sampling were all 12 staff of the Pharmacy Installation. The results obtained through the Fishbone Diagram were 13 root causes covering the aspects of Man, Money, Method, Machine, Material, and Environment. The priority of the root cause of stock-outs and drug stagnation in the Pharmacy Installation of Puri Bunda Mother and Child Hospital Malang is the suboptimal use of the Hospital Management Information System (HMIS). The possible solutions are conducting intensive training for Pharmacy Installation staff in using HMIS, developing HMIS related to drug procurement, as well as repairing warehouse and pharmacy installation facilities and infrastructure.